Spatial and Temporal Variability of Transplanted Rice At the Field Scale - Dobermann, Achim; Pampolino, Mirasol F.; Neue, Heinz-Ulrich (Wiley, 1995)
Measuring rice (Oryza sativa L.) growth in farmers' fields requires plant sampling techniques that take account of spatial and temporal variability. Our objective was to specify sampling recommendations for transplanted rice at the field scale. Rice was grown in two fields, fertilized and not, at 20‐ by 20‐cm hill spacings. Plant height, tiller number per hill, dry matter yield, and foliage area index were measured during the growth period at 8 locations and harvest samples were taken at 56 locations per field. Variation was low for plant height at all growth stages (CV = 6.1–9.5%); tiller number varied more (CV = 21–33%), especially in the tillering stage. Variation at harvest was intermediate (CV = 12–21%) for most crop variables. Grain yield ranged from 2.41 to 5.88 t ha−1 for the unfertilized field and 4.54 to 8.82 t ha−1 for the fertilized field. Transplanting errors introduced variation among hills. Variation between quadrats within a field was due to varying growth rates between tillering and panicle initiation (PI) and was related to the spatial distribution of inherent soil nutrient availability and fertilizer nutrient supply. Nonhomogeneous topdressed application of N caused location‐specific microvariation in crop stands. At all growth stages, two samples of three randomly selected hills were sufficient to measure plant height in a field. Increasing the number of samples had more effect on the precision of tiller number estimates than did increasing the size of the sampling unit. To measure tiller number between tillering and PI of rice, sampling units of five hills should be used and samples should be collected from 12 to 19 quadrats. At flowering, seven samples are enough. Harvest estimates of agronomic characters should be based on 8 to 12 quadrats when 10‐hill sampling units are used. A stratified random sampling design should be used, and samples should be taken >3 m apart.